Electrode paste, method of manufacture and back contact solar cell
Patent Information
- Application Number
- CN202611229836.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-07-08
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]现有技术为提高电性能,通常采用高活性玻璃体系提高浆料,但会损害电极在长期老化环境下的稳定性,而为了提升长期可靠性,采用反应温和的玻璃体系时,又难以实现理想的接触性能,导致电池的初始转换效率降低
[0009]本公开实施例中提供的一个或多个技术方案中,首先,电极浆料包括银基导电材料、混合玻璃材料和有机载体,混合玻璃材料包括第一玻璃材料、第二玻璃材料和第三玻璃材料,其中,第一玻璃材料的软化温度低于所述第二玻璃材料的软化温度。因此,在烧结过程中,第一玻璃材料较低的软化温度使其在烧结初期率先熔融,降低了浆料与SiNx等钝化层的接触电阻,为银基导电颗粒与硅基底的欧姆接触打通了通道,保障了电池的初始高转换效率。而第二玻璃材料较高的软化温度,在烧结的中后段高温区间才逐步软化,其前期的固态特性可有效限制第一玻璃材料的流动范围,避免了钝化层过度损伤或电极塌陷,第二玻璃材料后续还可以与熔融的第一玻璃材料形成互穿网络结构,既能够阻挡第一玻璃材料对钝化层和硅基底的过度侵蚀,又可以为电极提供稳固的结构支撑,保障了电极的几何形貌与机械结合强度。而第三玻璃材料中的高含量的TiO2,能与玻璃相形成稳定的固溶体,降低玻璃相的离子导电性,减少了长期高温高湿环境下银离子从电极向硅片或玻璃相内部迁移的风险,避免了电极出现空洞、熔断等失效现象。同时,TiO2能与硅片表面的SiO2形成Ti-O-Si键,强化玻璃相与硅片界面的结合强度,提高了界面层的致密度,从而抑制了界面开裂或剥离,而且还凭借自身优异的耐酸碱、抗紫外老化特性,增强了电极对高温、高湿、酸雨等户外严苛环境的耐受性,从而确保了背接触太阳能电池在全生命周期内性能的持久与可靠。
Smart Images

Figure CN123017596A_ABST
Abstract
Description
[0001] This disclosure claims priority to Chinese Patent Application No. 2026110138294, filed on July 8, 2026, entitled "An Electrode Paste and Preparation Method Thereof and a Back Contact Solar Cell", the entire contents of which are incorporated herein by reference. Technical Field
[0002] This disclosure relates to the field of photovoltaic cell technology, and in particular to an electrode paste and its preparation method and a back-contact solar cell. Background Technology
[0003] Back-contact (BC) solar cells integrate both positive and negative electrodes on the back of the cell, eliminating the light-shielding losses caused by the front-side metal grid lines. This represents a next-generation crystalline silicon solar cell technology for achieving higher photoelectric conversion efficiency. However, the performance of BC cells depends on the paste used for the back electrodes. This paste must be able to effectively penetrate the back passivation layer (such as SiNx) during sintering to form a low-resistance ohmic contact and achieve high conversion efficiency, while also ensuring excellent stability of the electrodes under long-term outdoor conditions such as high temperature, high humidity, and acid rain.
[0004] Existing technologies typically employ highly reactive glass systems to enhance slurry performance, but this can compromise the stability of the electrodes under long-term aging conditions. Conversely, while using milder glass systems to improve long-term reliability, achieving ideal contact performance is challenging, leading to a decrease in the initial conversion efficiency of the battery. Therefore, a trade-off exists between initial conversion efficiency and long-term stability, hindering the commercialization of BC batteries. Summary of the Invention
[0005] This disclosure is made in view of the above-mentioned problems. This disclosure provides an electrode paste and its preparation method, as well as a back-contact solar cell, which improves the long-term reliability of the electrode while providing electrical performance.
[0006] According to a first aspect of this disclosure, an electrode paste is provided, comprising: a silver-based conductive material, a mixed glass material, and an organic carrier, wherein the mixed glass material comprises a first glass material, a second glass material, and a third glass material, the first glass material comprising at least aluminum phosphate and / or zinc phosphate, and the third glass material comprising at least 10% to 20% TiO2 based on 100% of the total mass of the third glass material, and the softening temperature of the first glass material being lower than that of the second glass material.
[0007] According to a second aspect of this disclosure, a method for preparing an electrode paste is provided, comprising: The first glass material, the second glass material, and the third glass material are mixed to obtain a mixed glass material; The silver-based conductive material, the mixed glass material, and the organic carrier are mixed and then ground and dispersed to obtain the electrode slurry.
[0008] According to a third aspect of this disclosure, a back-contact solar cell is provided, wherein the electrodes of the back-contact solar cell are formed by printing and sintering the electrode paste described in the first aspect.
[0009] In one or more technical solutions provided in this disclosure, the electrode slurry firstly comprises a silver-based conductive material, a mixed glass material, and an organic carrier. The mixed glass material includes a first glass material, a second glass material, and a third glass material, wherein the softening temperature of the first glass material is lower than that of the second glass material. Therefore, during sintering, the lower softening temperature of the first glass material causes it to melt first in the early stages of sintering, reducing the contact resistance between the slurry and the passivation layer such as SiNx, thus opening a channel for ohmic contact between the silver-based conductive particles and the silicon substrate, ensuring the initial high conversion efficiency of the battery. The higher softening temperature of the second glass material means it gradually softens only in the high-temperature range of the later stages of sintering. Its early solid-state characteristics effectively limit the flow range of the first glass material, preventing excessive damage to the passivation layer or electrode collapse. The second glass material can also subsequently form an interpenetrating network structure with the molten first glass material, which can both prevent excessive erosion of the passivation layer and silicon substrate by the first glass material and provide stable structural support for the electrode, ensuring the geometric morphology and mechanical bonding strength of the electrode. The high TiO2 content in the third glass material forms a stable solid solution with the glass phase, reducing the ionic conductivity of the glass phase and migrating silver ions from the electrode into the silicon wafer or glass phase under long-term high temperature and humidity conditions. This prevents electrode failures such as voids and melting. Simultaneously, TiO2 forms Ti-O-Si bonds with SiO2 on the silicon wafer surface, strengthening the bonding strength between the glass phase and the silicon wafer interface and increasing the density of the interface layer. This inhibits interface cracking or peeling. Furthermore, its excellent acid and alkali resistance and UV aging resistance enhance the electrode's tolerance to harsh outdoor environments such as high temperature, high humidity, and acid rain, ensuring the long-lasting and reliable performance of the back-contact solar cell throughout its entire lifespan.
[0010] Therefore, the technical solution disclosed herein effectively solves the technical problem that existing back-contact battery electrode pastes are difficult to balance initial efficiency and long-term reliability, providing material support for the industrialization and promotion of next-generation high-efficiency crystalline silicon solar cells.
[0011] It should be understood that both the foregoing general description and the following detailed description are exemplary and intended to provide further illustration of the claimed technology. Attached Figure Description
[0012] The above and other objects, features, and advantages of this disclosure will become more apparent from the more detailed description of the embodiments thereof in conjunction with the accompanying drawings. The drawings are provided to further illustrate the embodiments of this disclosure and form part of the specification. They are used together with the embodiments of this disclosure to explain the disclosure and do not constitute a limitation thereof. In the drawings, the same reference numerals generally represent the same components or steps.
[0013] Figure 1 This is a flowchart illustrating the preparation process of the electrode paste according to an embodiment of this disclosure. Detailed Implementation
[0014] To make the objectives, technical solutions, and advantages of this disclosure more apparent, exemplary embodiments according to this disclosure will now be described in detail with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of this disclosure, and not all embodiments of this disclosure. It should be understood that this disclosure is not limited to the exemplary embodiments described herein.
[0015] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this disclosure, "multiple" means two or more, unless otherwise expressly specified. "Several" means one or more, unless otherwise expressly specified.
[0016] In the description of this disclosure, it should be understood that the terms "upper", "lower", "front", "rear", "left", "right", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing this disclosure and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this disclosure.
[0017] It should be noted that in this invention, the terms "exemplary" or "for example" are used to indicate examples, illustrations, or descriptions. Any embodiment or design described as "exemplary" or "for example" in this disclosure should not be construed as being more preferred or advantageous than other embodiments or designs. Specifically, the use of terms such as "exemplary" or "for example" is intended to present the relevant concepts in a concrete manner.
[0018] In this invention, "at least one" refers to one or more, and "more than one" refers to two or more. "And / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A alone, A and B simultaneously, or B alone, where A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects are in an "or" relationship. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, at least one of a, b, or c can represent: a, b, c, a combination of a and b, a combination of a and c, a combination of b and c, or a, b, and c, where a, b, and c can be single or multiple.
[0019] Electrical contact materials, as core functional materials for enabling circuit switching and current transmission in electrical equipment, have irreplaceable and widespread applications in many key fields such as household appliances, automotive electronics, new energy equipment, energy storage systems, 5G communication facilities, and aerospace. Their performance directly affects the operational stability, safety, and service life of various electrical devices such as high-voltage switches, relays, circuit breakers, and contactors, making them a crucial link in ensuring the normal operation of the entire electrical system.
[0020] Back-contact batteries, by placing all electrodes on the back of the battery, eliminate the light-shielding loss of the front metal grid lines and are considered the next-generation crystalline silicon battery technology for achieving higher photoelectric conversion efficiency.
[0021] However, the performance of BC batteries is highly dependent on their back electrode paste. This paste needs to meet two requirements simultaneously: First, it needs to effectively penetrate the back passivation layer (such as SiNx) during sintering to form a low-resistance ohmic contact, thereby obtaining a high fill factor and initial conversion efficiency. Second, it needs to ensure that the formed electrode has excellent chemical and mechanical stability under harsh outdoor environments such as long-term high temperature, high humidity, and acidity, in order to maintain the long-term power output of the battery.
[0022] Currently, the core technical challenge of BC batteries lies in the irreconcilable contradiction between initial electrical performance and long-term reliability. To achieve high initial efficiency, highly reactive glass frit systems are typically employed, but this often leads to degradation of the electrode-semiconductor interface during long-term aging, affecting the battery's weather resistance. Conversely, choosing a milder glass frit system to improve long-term reliability often results in difficulties in achieving sufficient and uniform contact, leading to increased contact resistance and reduced initial conversion efficiency.
[0023] To address the aforementioned issues, this disclosure provides an electrode paste, its preparation method, and a back-contact solar cell. Through the synergistic effect of three functionally complementary glass systems, the electrode paste significantly improves the long-term reliability of the electrode under harsh environments while ensuring high electrical performance. It should be understood that this electrode paste is suitable for the N-type electrode of a back-contact (BC) cell.
[0024] This disclosure provides an electrode paste comprising a silver-based conductive material, a mixed glass material, and an organic carrier. The mixed glass material comprises a first glass material, a second glass material, and a third glass material. The first glass material comprises at least aluminum phosphate and / or zinc phosphate. The third glass material comprises at least 10% to 20% TiO2, based on the total mass of the third glass material being 100%. The softening temperature of the first glass material is lower than that of the second glass material.
[0025] During the sintering process of the aforementioned electrode slurry, the first glass material, due to its lower softening temperature, melts first in the initial stage of sintering. This reduces the contact resistance between the slurry and the passivation layer such as SiNx, opening a channel for ohmic contact between the silver-based conductive particles and the silicon substrate, ensuring the initial high conversion efficiency of the battery. The second glass material, due to its higher softening temperature, gradually softens only in the high-temperature range of the later stages of sintering. Its initial solid-state characteristics effectively limit the flow range of the first glass material, preventing excessive damage to the passivation layer or electrode collapse. The second glass material can subsequently form an interpenetrating network structure with the molten first glass material, both preventing excessive erosion of the passivation layer and silicon substrate by the first glass material and providing stable structural support for the electrode, ensuring the electrode's geometry and mechanical bonding strength. The high TiO2 content in the third glass material forms a stable solid solution with the glass phase, reducing the ionic conductivity of the glass phase and minimizing the risk of silver ions migrating from the electrode to the silicon wafer or glass phase under long-term high-temperature and high-humidity conditions, thus preventing electrode failure phenomena such as voids and melting. Meanwhile, TiO2 can form Ti-O-Si bonds with SiO2 on the silicon wafer surface, strengthening the bonding strength between the glass phase and the silicon wafer interface and increasing the density of the interface layer, thereby inhibiting interface cracking or peeling. Moreover, with its excellent acid and alkali resistance and UV aging resistance, it can enhance the electrode's tolerance to harsh outdoor environments such as high temperature, high humidity, and acid rain, thus ensuring the long-lasting and reliable performance of the back contact solar cell throughout its entire life cycle.
[0026] For example, the third glass material described above includes at least 10% to 20% TiO2, such as at least 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or 20% TiO2. In this disclosure, the content of TiO2 in the third glass material is not limited to the specific numerical points listed above, but can continuously vary within the range of 10% to 20%. That is, as long as the content of TiO2 falls within the range of 10% to 20% (inclusive of the two endpoints), the technical effects of this disclosure can be achieved.
[0027] Preferably, the third glass material contains at least 10% to 14% TiO2, and the content of TiO2 is further preferably 10% to 14%. This can ensure the stability of the glass phase structure while further optimizing its effect on inhibiting ion migration and improving the interfacial bonding strength, thereby achieving better long-term reliability.
[0028] In some examples, with the total mass of the mixed glass powder being 100%, the mass content of the first glass material is 10% to 40%, the mass content of the second glass material is 50% to 89%, and the mass content of the third glass material is 1% to 10%.
[0029] In the aforementioned mixed glass powder, the 10%–40% first glass material ensures a sufficient amount of low-temperature active phase in the initial sintering stage, guaranteeing effective penetration of the passivation layer and the formation of low-resistance contact, while avoiding excessive corrosion due to excessive content. The 50%–89% second glass material, as the main framework phase, fully exerts its structural support and corrosion control functions, ensuring electrode forming quality and mechanical strength. Its high proportion lays the foundation for electrode structural stability. The 1%–10% third glass material, with a low proportion and a composition containing 10%–20% TiO2, achieves multiple effects such as suppression of glass phase ionic conductivity, strengthening of interface bonding, and improvement of weather resistance, avoiding a decrease in the overall activity of the glass phase due to excessive third glass material. Therefore, this mixed glass system enables the electrode slurry to not only have a wide process window suitable for industrial sintering processes, but also improves both the initial conversion efficiency and long-term stability of the battery, achieving a performance balance that was previously difficult to achieve simultaneously.
[0030] In one alternative embodiment, the first glass material further includes TeO2, PbO, B2O3, and a flux. Based on the total mass of the first glass material (100%), the mass content of TeO2 is 20%–63%, the mass content of PbO is 20%–40%, the mass content of B2O3 is 1%–10%, the mass content of aluminum phosphate and / or zinc phosphate is 0.5%–1.5%, and the mass content of the flux is 10%–30%. The introduction of a specific ratio of TeO2, PbO, B2O3, and flux into the first glass material can form a synergistic low-temperature active system with aluminum phosphate / zinc phosphate, further optimizing the sintering reaction characteristics and interfacial contact performance of the slurry.
[0031] For example, taking the total mass of the first glass material as 100%, the mass content of the aluminum phosphate and / or zinc phosphate can be 0.5%, 0.85%, 1.0%, 1.2%, or 1.5%. In this disclosure, the content of aluminum phosphate and / or zinc phosphate in the first glass material is not limited to the specific numerical points listed above, but can be selected in the range of 0.5% to 1.5%. That is, as long as the content of aluminum phosphate and / or zinc phosphate falls within the range of 0.5% to 1.5% (including the two endpoints), the technical effect of this disclosure can be achieved.
[0032] Specifically, the combination of 20%–63% TeO2 and 20%–40% PbO significantly reduces the softening temperature and melt viscosity of the first glass material, improving its fluidity and wettability in the early stages of sintering. This allows it to more quickly and uniformly wet the silver-based conductive particles and the passivation layer surface, enhancing its ability to erode the passivation layer and further reducing ohmic contact resistance, thus improving the initial conversion efficiency of the battery. Meanwhile, 1%–10% B2O3, as a glass network forger, optimizes the structural compactness of the glass phase, preventing high-temperature crystallization or a porous structure caused by excessively lowering the softening temperature.
[0033] For example, based on the total mass of the first glass material as 100%, the mass content of the above-mentioned TeO2 is preferably 30% to 63%, more preferably 35% to 61%, and even more preferably 38.6% to 60.2%.
[0034] In some examples, the flux mentioned above includes at least one of Li₂O, Na₂O, K₂O, ZnO, MgO, CaO, SrO, and BaO. By introducing a flux, the melting temperature and viscosity of the first glass material can be further reduced, enhancing its wetting and penetration ability into the passivation layer during the initial sintering stage. Simultaneously, it helps to control the overall thermal expansion coefficient of the glass phase, improve its thermal compatibility with the silicon substrate, and reduce interfacial thermal stress, thereby improving the adhesion strength and long-term thermal cycling reliability of the electrode.
[0035] In one feasible embodiment, the second glass material comprises TeO2, PbO, Bi2O3, SiO2, WO3, TiO2, ZnO, alkali metal oxides, and alkaline earth metal oxides. Based on the total mass of the second glass material as 100%, the mass content of TeO2 is 15%–35%, the mass content of PbO is 15%–35%, the mass content of Bi2O3 is 10%–25%, the mass content of SiO2 is 15%–30%, the mass content of WO3 is 0%–10%, the mass content of TiO2 is 0%–5%, the mass content of ZnO is 1%–10%, the mass content of alkali metal oxides is 10%–25%, and the mass content of alkaline earth metal oxides is 0%–10%.
[0036] Specifically, the second glass material employs a multi-component system including TeO2, PbO, Bi2O3, and SiO2 to construct a high-performance framework phase suitable for the high-temperature range in the later stages of sintering, further enhancing the synergistic advantages of the mixed glass system. Specifically, the combination of 15%–35% TeO2 and 15%–35% PbO allows for the control of the softening temperature of the second glass material, making it higher than that of the first glass material and matching the high-temperature window of industrial sintering. This ensures both the solid-state support morphology in the early stages of sintering and appropriate melting at high temperatures, forming a highly compatible interpenetrating network with the first glass material. The synergistic combination of 10%–25% Bi2O3 and 15%–30% SiO2, with SiO2 acting as the glass network former, significantly improves the structural strength and thermal stability of the glass phase, while Bi2O3 optimizes the melt flowability of the glass phase, avoiding the embrittlement problem caused by excessive SiO2 content, thus ensuring the mechanical flexibility and bonding strength of the electrode.
[0037] Building upon this, if the second glass material contains WO3 and TiO2, it can further optimize the chemical stability and interfacial compatibility of the glass phase. The 10%–25% alkali metal oxides and 1%–10% alkaline earth metal oxides can adjust the thermal expansion coefficient of the glass phase, making it more compatible with the thermal expansion coefficients of the first glass material, the third glass material, and the silicon substrate. This significantly reduces residual interfacial stress during sintering and cooling, minimizing the risk of electrode cracking. Therefore, this second glass material helps form a continuous and dense glass framework in the later stages of sintering, thereby providing reliable structural support for the electrode and optimizing its thermomechanical properties.
[0038] In some examples, the aforementioned second glass material also includes a silver-containing material, which includes at least one of elemental silver, silver nitrate, and silver oxide. On one hand, the silver-containing material decomposes or melts during the high-temperature sintering stage, releasing silver atoms that can form a synergistic conductive effect with the silver-based conductive particles in the slurry, filling the tiny gaps between the silver-based conductive particles and improving the density and adhesion strength of the electrode. On the other hand, the silver atoms in the silver-containing material can diffuse to the interface between the electrode and the silicon substrate, forming a tighter contact site with the silicon, optimizing the interfacial carrier transport efficiency, forming a more continuous conductive channel, and further reducing the contact resistance.
[0039] In some examples, the aforementioned alkali metal oxides include two or more of Li₂O, Na₂O, and K₂O.
[0040] In other examples, the aforementioned alkaline earth metal oxides include at least one of MgO, CaO, SrO, and BaO.
[0041] For example, the particle size D50 of the second glass material is 1μm to 2μm.
[0042] In some feasible embodiments, the aforementioned third glass material further includes SiO2, B2O3, WO3, Al2O3, ZnO, TeO2, Bi2O3, PbO, and CuO. Based on the total mass of the third glass material as 100%, the mass content of SiO2 is 30%–50%, the mass content of B2O3 is 5%–15%, the mass content of WO3 is 5%–15%, the mass content of Al2O3 is 5%–10%, the mass content of ZnO is 5%–15%, the total mass content of TeO2, Bi2O3, and PbO is 5%–20%, and the mass content of CuO is 5%–15%. Among them, SiO2, as the core framework of the glass network, can significantly improve the structural compactness and thermal stability of the third glass material, providing a stable carrier for TiO2 to play a long-term protective role. B2O3 can optimize the melt compatibility of the glass phase, promote the interpenetration and fusion of the third glass material with the first and second glass materials, and avoid the appearance of cracks or delamination at the interface. WO3, Al2O3, and ZnO can further adjust the thermal expansion coefficient of the glass phase, making the glass phase more compatible with silver-based conductive materials and silicon substrates, greatly reducing the residual stress at the interface after sintering and cooling, and suppressing the risk of interface cracking.
[0043] Meanwhile, the TeO2, Bi2O3 and PbO in the third glass material can optimize the interfacial reactivity of the third glass material, help TiO2 and SiO2 on the silicon wafer surface to form more uniform Ti-O-Si bonds, and strengthen the interfacial bonding strength. CuO can work synergistically with TiO2 to improve the glass phase's resistance to acid and alkali corrosion and enhance the electrode's tolerance to harsh outdoor environments such as acid rain and high humidity.
[0044] In some examples, the third glass material described above, based on the total mass of the third glass material as 100%, has a TeO2 mass content of 8% to 13%, a Bi2O3 mass content of 4% to 5%, and a PbO mass content of 3% to 5%.
[0045] In one example, the oxides in the first, second, and third glass materials can be introduced in various forms such as oxides, carbonates, sulfates, hydroxides, and organic compounds, without limitation here.
[0046] In some alternative methods, the aforementioned silver-based conductive material is silver powder, which includes at least one of micron-sized spherical silver powder, micron-sized flake silver powder, dendritic silver powder, and nano-sized spherical silver powder. Micron-sized spherical silver powder provides good dispersibility and filling properties; micron-sized flake silver powder forms efficient planar conductive pathways through layer stacking; dendritic silver powder utilizes its high specific surface area and branched structure to enhance the mechanical interlocking and electrical contact between particles; and nano-sized spherical silver powder effectively fills the gaps between micron-sized silver powders, improving the electrode's density and conductive uniformity. The combined use of silver powders with various morphologies reduces the electrode's bulk resistance and contact resistance, thereby further improving the electrode's mechanical adhesion and long-term reliability while ensuring high conductivity.
[0047] For example, taking the total mass of the aforementioned silver-based conductive material as 100%, the mass content of micron-sized spherical silver powder is not less than 80%, and the mass content of nano-sized spherical silver powder is 5%~20%. The micron-sized spherical silver powder, with a mass content of not less than 80%, utilizes its regular spherical morphology and good stacking properties to form a continuous and dense main conductive path inside the electrode, ensuring basic conductivity and printability. The 5%~20% nano-sized spherical silver powder, as a functional reinforcing phase, can fully adhere to the surface and interparticle spaces of the micron-sized silver powder. Utilizing the high surface activity and low-temperature sintering effect of nanoparticles, it melts first during sintering, promoting the fusion between micron-sized silver powder particles, further reducing the bulk resistance and contact resistance of the electrode, and improving carrier transport efficiency. Thus, while improving electrode conductivity, it also enhances mechanical strength and resistance to environmental corrosion.
[0048] For example, the particle size D50 of the aforementioned micron-sized spherical silver powder and micron-sized flake silver powder is 1μm~5μm, while the particle size D50 of the nano-sized spherical silver powder is 200nm~800nm. The 1μm~5μm micron-sized silver powder can form a stable and continuous conductive framework, ensuring the electrode has low bulk resistance and good mechanical support. Meanwhile, the 200nm~800nm nano-sized spherical silver powder can efficiently fill the gaps between the micron-sized silver powders, significantly improving the electrode density and interfacial contact quality. Its higher specific surface area also enhances sintering activity, promoting the formation of a more complete conductive network at low temperatures. Therefore, this particle size, while ensuring good printability and process window of the paste, provides a material basis for achieving highly conductive, highly adhesive, and highly reliable back-contact solar cell electrodes.
[0049] The aforementioned organic carriers may include organic solvents, resins, dispersants, and functional additives.
[0050] The organic solvents mentioned above can be selected from at least one of terpineol, diethylene glycol butyl ether, butyl carbitol, benzyl alcohol, and propylene glycol methyl ether acetate, and are used to adjust the rheological properties and drying rate of the slurry.
[0051] The resin can be selected from at least one of ethyl cellulose, acrylic resin, nitrocellulose, and polyvinyl butyral, and serves as a binder phase to provide slurry film-forming properties and electrode adhesion strength.
[0052] The dispersant mentioned above can be selected from at least one of phosphate esters, fatty acid derivatives, and polymeric dispersants, and is used to improve the dispersion stability of inorganic particles in the system.
[0053] The aforementioned functional additives include at least one of leveling agents, defoamers, and coupling agents, used to optimize the printability, surface condition, and interfacial bonding properties of the paste. It should be understood that leveling agents, defoamers, and coupling agents can be selected from conventional additives, and are not limited here.
[0054] Through the synergistic effect of the above components, the organic carrier can provide the slurry with suitable viscosity, thixotropy, storage stability and printability, and ensure the smooth removal of organic matter during sintering, ultimately obtaining a dense, flat and firmly bonded electrode structure.
[0055] This disclosure also provides a method for preparing an electrode paste, which can be used to prepare the electrode paste of this disclosure. Figure 1 A flowchart illustrating the preparation process of the electrode paste according to an embodiment of this disclosure is shown, as follows: Figure 1 As shown, the method for preparing the electrode paste according to an embodiment of this disclosure includes: Step 101: Mix the first glass material, the second glass material and the third glass material to obtain a mixed glass material.
[0056] For example, the above-mentioned mixing of the first glass material, the second glass material, and the third glass material to obtain a mixed glass material specifically includes: First, drying the first glass material, the second glass material, and the third glass material respectively to remove adsorbed moisture and avoid introducing air bubbles or affecting the dispersion uniformity during subsequent mixing and slurry preparation. Then, weighing the three glass materials according to a preset mass ratio and placing them in a dry powder mixing device for mechanical mixing at room temperature until a uniform glass powder mixture is obtained. Next, sieving the mixed glass powder to remove large particles formed due to static electricity or agglomeration, resulting in a mixed glass material with uniform particle size distribution and thorough mixing.
[0057] Step 102: Mix the silver-based conductive material, the mixed glass material, and the organic carrier, and then grind and disperse them to obtain the electrode slurry.
[0058] For example, the above-mentioned mixing of silver-based conductive material, mixed glass material, and organic carrier, followed by grinding and dispersion to obtain electrode slurry, specifically includes: first, mixing and grinding the mixed glass material with a portion of the organic carrier to form a glass slurry; then, mixing the glass slurry, silver-based conductive material, and the remaining organic carrier, followed by stirring and grinding to disperse, ultimately obtaining a uniform and stable electrode slurry.
[0059] This disclosure also discloses a back-contact solar cell, wherein the electrodes of the back-contact solar cell are formed by printing and sintering the electrode paste of this disclosure embodiment. In this back-contact solar cell, the N-region electrode is formed using the electrode paste provided in this disclosure embodiment, and the P-region electrode can be formed using commercially available BC battery P-region paste. No specific model is limited here, and those skilled in the art can choose accordingly. The printing can be done using conventional screen printing, and the width of the printed electrode is the conventional width of BC batteries in the art (10μm~40μm). This width is a common design parameter in the industry and can be freely adjusted by those skilled in the art. The sintering temperature can be 720℃±20℃. After sintering, the line height of the formed N-region electrode is 4.5μm~5μm, and the line height of the P-region electrode is 5μm~5.5μm.
[0060] In summary, the electrode paste, preparation method, and back-contact solar cell of this disclosure utilize a hybrid glass system composed of a first glass material, a second glass material, and a third glass material. The first glass material, with aluminum phosphate / zinc as its core, achieves controllable and uniform erosion of the SiNx passivation layer through an optimized TeO2-PbO-B2O3-flux ratio, ensuring excellent ohmic contact and initial conversion efficiency. The second glass material, as the main component, provides process stability and structural support, preventing excessive interfacial reactions. The third glass material, incorporating high levels of TiO2 and CuO, significantly suppresses ion migration and enhances interfacial bonding strength, thereby giving the electrode excellent resistance to high temperature and humidity and environmental corrosion. Therefore, the combination of these three glass materials solves the long-standing problem in the field of back-contact solar cell electrodes of the difficulty in simultaneously achieving high initial electrical performance and high long-term reliability, providing a reliable material foundation and technical support for promoting the industrialization of high-efficiency, long-life back-contact solar cells.
[0061] To verify the effectiveness of the electrode paste provided in the embodiments of the present invention, the embodiments of the present invention are demonstrated by comparing the embodiments with comparative examples.
[0062] Example 1 The specific raw materials used in this first embodiment are as follows: Silver-based conductive material: 81.5 wt% micron-sized spherical silver powder AG1 (D50=2.2±0.1μm) and 4.5 wt% nano-sized spherical silver powder AG2 (D50=700±100nm).
[0063] Glass material: The first glass material is GA-1 (by weight, it consists of: 48.5 parts TeO2, 32 parts PbO, 1 part B2O3, 0.5 parts Zn3(PO4)2, 13 parts Li2O, and 5 parts Na2O).
[0064] The second glass material is GB-1 (by weight, the composition is: 18 parts TeO2, 20 parts PbO, 13 parts Bi2O3, 17 parts SiO2, 5.5 parts WO3, 15 parts Li2O, 5.5 parts Na2O, 5 parts ZnO, and 1 part AgNO3).
[0065] The third glass material is GC-1 (by weight, it consists of: 30 parts SiO2, 7 parts B2O3, 14 parts WO3, 6 parts Al2O3, 8 parts ZnO, 13 parts TeO2, 4 parts Bi2O3, 3 parts PbO, 10 parts TiO2, and 5 parts CuO).
[0066] Organic carrier Y: Based on the total mass of the organic carrier (100%), the composition is 51.11 wt% terpineol, 21.67 wt% diethylene glycol butyl ether acetate, 8.9 wt% ethyl cellulose (EC-N22), 8.45 wt% ethyl cellulose (EC-N7), 4.78 wt% hydrogenated castor oil, 2.89 wt% oleic acid, 1.1 wt% dispersant BYK-180, and 1.1 wt% silane coupling agent (KH-560).
[0067] Embodiment 1 of this disclosure provides a method for preparing electrode paste, which specifically includes the following steps: The first step involves mixing and stirring the GA-1 raw materials evenly, transferring them to a platinum crucible, and melting them in a 1000℃ high-temperature furnace for 30 minutes. After melting, the mixture is poured out, cold-rolled, and then ball-milled to a particle size of D50 = 1.0 ± 0.1 μm to obtain the first glass material. The second step involves mixing and stirring the GB-1 raw materials evenly, transferring them to a platinum crucible, and melting them in a 1100℃ high-temperature furnace for 30 minutes. After melting, the mixture is poured out, cold-rolled, and then ball-milled to a particle size of D50 = 1.5 ± 0.1 μm to obtain the second glass material. The third step involves mixing and stirring the GC-1 raw materials evenly, transferring them to a platinum crucible, and melting them in a 1400℃ high-temperature furnace for 60 minutes. After melting, the mixture is poured out, cold-rolled, and then ball-milled to a particle size of D50 = 1.8 ± 0.1 μm to obtain the third glass material.
[0068] The second step involves weighing 1.8 wt% of the first glass material (GA-1), 2.7 wt% of the second glass material (GB-1), and 0.5 wt% of the third glass material (GC-1), and mixing them evenly to obtain a mixed glass material.
[0069] The third step involves weighing 81.5 wt% silver powder AG1, 4.5 wt% silver powder AG2, the above-mentioned mixed glass material (total 5 wt%), and 9 wt% organic carrier Y according to the specified ratio. All components are mixed and first pre-mixed by centrifugation, and then fully ground and dispersed using a three-roll mill to finally obtain a uniform and stable electrode slurry.
[0070] Example 2 Embodiment 2 of this disclosure provides a method for preparing an electrode slurry. The slurry uses the same components as the silver-based conductive material (AG1, AG2), glass material (GA-1, GB-1, GC-1), and organic carrier as in Embodiment 1, differing only in the mass percentage of each component in the final slurry. The details are as follows: 78 wt% silver powder AG1, 8 wt% silver powder AG2, 5 wt% mixed glass material (composed of 1.8 wt% GA-1, 2.7 wt% GB-1 and 0.5 wt% GC-1), and 9 wt% organic carrier Y.
[0071] Example 3 This disclosure provides a method for preparing an electrode paste in Embodiment 3. The only difference between the raw materials used in Embodiment 3 and Embodiment 1 is that the first glass material is replaced by GA-2 instead of GA-1. By weight, the chemical composition of GA-2 is: 60.2 parts of TeO2, 21.8 parts of PbO, 1.5 parts of B2O3, 1.5 parts of Zn3(PO4)2, 11.6 parts of Li2O, and 3.4 parts of Na2O. The mass percentage of each component in the final paste of Embodiment 3 is the same as that in Embodiment 1.
[0072] Example 4 This disclosure provides a method for preparing an electrode paste in Embodiment 4. The only difference between the raw materials used in Embodiment 4 and Embodiment 1 is that the first glass material is replaced by GA-3 instead of GA-1. By weight, the chemical composition of GA-3 is: 38.6 parts TeO2, 39.6 parts PbO, 2.2 parts B2O3, 1 part AlPO4, 15.6 parts Li2O, 3 parts Na2O, and 1 part K2O. The mass percentage of each component in the final paste of Embodiment 4 is the same as that in Embodiment 1.
[0073] Example 5 This disclosure provides a method for preparing an electrode paste in Embodiment 5. The only difference between the raw materials used in Embodiment 5 and Embodiment 1 is that the second glass material is replaced by GB-2 instead of GB-1. By weight, the chemical composition of GB-2 is: 18 parts TeO2, 30.5 parts PbO, 15.5 parts Bi2O3, 17 parts SiO2, 8 parts Li2O, 2 parts Na2O, 5 parts ZnO, 2 parts BaO, and 2 parts Ag2O. The mass percentage of each component in the final paste of Embodiment 5 is the same as that in Embodiment 1.
[0074] Example 6 This disclosure provides a method for preparing an electrode paste in Embodiment Six. The only difference between the raw materials used in Embodiment Six and Embodiment One is that the second glass material is replaced by GB-3 instead of GB-1. By weight, the chemical composition of GB-3 is: 26 parts TeO2, 19 parts PbO, 12.8 parts Bi2O3, 24.5 parts SiO2, 3 parts WO3, 10.7 parts Li2O, 2 parts Na2O, 1 part ZnO, and 1 part Ag2O. The mass percentage of each component in the final paste of Embodiment Six is the same as that in Embodiment One.
[0075] Example 7 This disclosure provides a method for preparing an electrode paste in Embodiment Seven. The only difference between the raw materials used in Embodiment Seven and Embodiment One is that the third glass material is replaced by GC-2 instead of GC-1. By weight, the chemical composition of GC-2 is: 40.5 parts SiO2, 5 parts B2O3, 8 parts WO3, 6 parts Al2O3, 6.5 parts ZnO, 8 parts TeO2, 4 parts Bi2O3, 3 parts PbO, 14 parts TiO2, and 5 parts CuO. The mass percentage of each component in the final paste of Embodiment Seven is the same as that in Embodiment One.
[0076] Example 8 This disclosure provides an embodiment eight method for preparing an electrode paste. The only difference between the raw materials used in embodiment eight and embodiment one is that the third glass material is replaced by GC-3 instead of GC-1. By weight, the chemical composition of GC-3 is: 40 parts SiO2, 5.7 parts B2O3, 6 parts WO3, 6.2 parts Al2O3, 7.1 parts ZnO, 13 parts TeO2, 4 parts Bi2O3, 3 parts PbO, 10 parts TiO2, and 5 parts CuO. The mass percentage of each component in the final paste of embodiment eight is the same as that in embodiment one.
[0077] Comparative Example 1 This Comparative Example 1 provides a method for preparing a comparative electrode slurry. The raw materials used in Comparative Example 1 and Example 1 are the same, as are the mass percentages of each component in the final slurry. The only difference is that the first glass material is replaced by the comparative glass material GD-1 instead of GA-1. By weight, the chemical composition of GD-1 is: 48.5 parts TeO2, 32 parts PbO, 1 part B2O3, 13 parts Li2O, and 5 parts Na2O. Compared to GA-1, this composition only lacks the Zn3(PO4)2 component.
[0078] Comparative Example 2 Comparative Example 2 provides a method for preparing a comparative electrode slurry. The raw materials used in Comparative Example 2 are the same as those in Example 1, and the mass percentages of each component in the final slurry are the same. The only difference is that the third glass material is replaced by comparative glass material GD-3 instead of GC-1. By weight, the chemical composition of GD-3 is: 30 parts SiO2, 7 parts B2O3, 14 parts WO3, 6 parts Al2O3, 8 parts ZnO, 13 parts TeO2, 4 parts Bi2O3, 3 parts PbO, and 5 parts CuO. Compared to GC-1, this composition only removes the TiO2 component.
[0079] Comparative Example 3 Comparative Example 3 provides a method for preparing a comparative electrode slurry. The raw materials used in Comparative Example 3 and Example 4 are the same, as are the mass percentages of each component in the final slurry. The only difference is that the first glass material is replaced by comparative glass material GD-2 instead of GA-3. By weight, the chemical composition of GD-2 is: 38.6 parts TeO2, 39.6 parts PbO, 2.2 parts B2O3, 15.6 parts Li2O, 3 parts Na2O, and 1 part K2O. Compared to GA-3, this composition only lacks the AlPO4 component.
[0080] Comparative Example 4 Comparative Example 4 provides a method for preparing a comparative electrode slurry. The raw materials used in Comparative Example 4 and Example 7 are the same, as are the mass percentages of each component in the final slurry. The only difference is that the third glass material is replaced by comparative glass material GD-4 instead of GC-2. By weight, the chemical composition of GD-4 is: 40.5 parts SiO2, 5 parts B2O3, 8 parts WO3, 6 parts Al2O3, 6.5 parts ZnO, 8 parts TeO2, 4 parts Bi2O3, 3 parts PbO, and 5 parts CuO. Compared to GC-2, this composition only removes the TiO2 component.
[0081] Comparative Example 5 Comparative Example 5 provides a method for preparing a comparative electrode slurry. The types of raw materials used in Comparative Example 5 are the same as those in Example 1, and the mass percentage of each component in the final slurry is the same. The difference is that two glass materials are replaced at the same time: the first glass material is replaced by the comparative glass material GD-1 instead of GA-1, and the third glass material is replaced by the comparative glass material GD-3 instead of GC-1.
[0082] By weight, the chemical composition of GD-1 is: 48.5 parts TeO2, 32 parts PbO, 1 part B2O3, 13 parts Li2O, and 5 parts Na2O. Compared with GA-1, this composition only removes the Zn3(PO4)2 component.
[0083] By weight, the chemical composition of GD-3 is: 30 parts SiO2, 7 parts B2O3, 14 parts WO3, 6 parts Al2O3, 8 parts ZnO, 13 parts TeO2, 4 parts Bi2O3, 3 parts PbO, and 5 parts CuO. Compared with GC-1, this composition only removes the TiO2 component.
[0084] The electrode pastes obtained in the above embodiments and comparative examples were printed onto the N region of a BC battery to obtain N region electrodes. The P region electrodes were obtained by printing the same paste onto the P region of the BC battery. After sintering at 720±20℃, N region electrodes with a line height of 4.5μm~5μm and P region electrodes with a line height of 5μm~5.5μm were obtained. These were tested under standard test conditions (STC: 25℃, 1000W / m). 2 The electrical performance of the BC battery, including its conversion efficiency (Eff), was tested under AM1.5G spectrum. The printing process employed conventional screen printing. This embodiment of the disclosure verifies the impact of the N-region electrode paste on the overall electrical performance of the battery.
[0085] Two BC solar cells from each of the above-described embodiments and comparative examples were subjected to an acetic acid test to assess their acetic acid resistance. Two BC solar cells from each of the above-described embodiments and comparative examples were also subjected to a PCT simulation test to assess their long-term stability.
[0086] Acetic acid test method: Add 58 ml of acetic acid to 1 liter of distilled water, then add 3.5 g of NaCl and mix thoroughly. Place the mixture into a container, insert the battery cells into the slotted tray, and place the container in the specified size. After placing the battery cells, seal with a film and transfer to an 85℃ oven for 4 hours. After the time is up, remove the container and test its IV electrical performance, calculating the acetic acid decay.
[0087] Simulated PCT test method: Place the solar cell in the PCT test furnace, set the temperature to 121±2℃, relative humidity to 100% RH, pressure to 0.2MPaG, and test duration to 24 hours.
[0088] The test results are shown in Table 1: Table 1
[0089] As can be seen from the data of the above embodiments and comparative examples, all embodiments of this disclosure (Embodiments 1 to 8) exhibit excellent and balanced comprehensive performance. The initial conversion efficiency of all embodiments is above 27.28%, which is at a high level. At the same time, the acetic acid decay rate of all embodiments is less than 6%, and the PCT decay rate is less than 17%, which reflects excellent long-term environmental reliability. This shows that this disclosure achieves synergistic optimization of high initial efficiency and high long-term reliability through a ternary hybrid glass material system.
[0090] The comparison between Comparative Example 1 (using GD-1 instead of GA-1) and Example 1, and the comparison between Comparative Example 3 (using GD-2 instead of GA-3) and Example 4, show that although the long-term reliability does not change much after the phosphate is missing, the initial conversion efficiency shows a decrease or no significant increase. This indicates that aluminum phosphate / zinc phosphate in the first glass material can improve the initial electrical performance of the battery.
[0091] The comparisons between Comparative Example 2 (using GD-3 instead of GC-1) and Example 1, and Comparative Example 4 (using GD-4 instead of GC-2) and Example 7, show that the initial efficiency is not significantly affected by the absence of TiO2, but the acetic acid decay rate increases sharply to 52.22% and 61.01%, and the PCT decay rate increases to 66.37% and 76.83%, indicating poor long-term reliability. This demonstrates that TiO2 in the third glass material is a key component for ensuring the long-term environmental stability of the electrode. Comparative Example 5, lacking both phosphate and TiO2, exhibits the worst long-term reliability, further proving that the ternary hybrid glass system of this invention can simultaneously address both efficiency and reliability.
[0092] The basic principles of this disclosure have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in this disclosure are merely examples and not limitations, and should not be considered as essential features of each embodiment of this disclosure. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the scope of this disclosure to the necessity of employing the aforementioned specific details for implementation.
[0093] The block diagrams of devices, apparatuses, devices, and systems disclosed herein are merely illustrative examples and are not intended to require or imply that they must be connected, arranged, or configured in the manner shown in the block diagrams. As those skilled in the art will recognize, these devices, apparatuses, devices, and systems can be connected, arranged, and configured in any manner. Words such as “comprising,” “including,” “having,” etc., are open-ended terms meaning “including but not limited to,” and are used interchangeably with them. The terms “or” and “and” as used herein refer to the terms “and / or,” and are used interchangeably with them unless the context clearly indicates otherwise. The term “such as” as used herein refers to the phrase “such as but not limited to,” and is used interchangeably with it.
[0094] Additionally, as used herein, the "or" used in a list of items beginning with "at least one" indicates a separate list, such that a list of, for example, "at least one of A, B, or C" means A or B or C, or AB or AC or BC, or ABC (i.e., A and B and C). Furthermore, the word "exemplary" does not imply that the described example is preferred or better than other examples.
[0095] It should also be noted that in the systems and methods of this disclosure, the components or steps can be decomposed and / or recombined. These decompositions and / or recombinations should be considered as equivalent solutions to this disclosure.
[0096] Various changes, substitutions, and modifications can be made to the technology described herein without departing from the teachings defined by the appended claims. Furthermore, the scope of the claims of this disclosure is not limited to the specific aspects of the processes, machines, manufactures, events, means, methods, and actions described above. Currently existing or later-developed processes, machines, manufactures, events, means, methods, or actions that perform substantially the same function or achieve substantially the same result as the corresponding aspects described herein can be utilized. Therefore, the appended claims include such processes, machines, manufactures, events, means, methods, or actions within their scope.
[0097] The above description of the disclosed aspects is provided to enable any person skilled in the art to make or use this disclosure. Various modifications to these aspects will be readily apparent to those skilled in the art, and the general principles defined herein may be applied to other aspects without departing from the scope of this disclosure. Therefore, this disclosure is not intended to be limited to the aspects shown herein, but rather to be carried out within the widest scope consistent with the principles and novel features disclosed herein.
[0098] The above description has been given for purposes of illustration and description. Furthermore, this description is not intended to limit the embodiments of this disclosure to the forms disclosed herein. Although numerous exemplary aspects and embodiments have been discussed above, those skilled in the art will recognize certain variations, modifications, alterations, additions, and sub-combinations therein.
Claims
1. An electrode paste, characterized in that, include: The invention comprises a silver-based conductive material, a mixed glass material, and an organic carrier. The mixed glass material includes a first glass material, a second glass material, and a third glass material. The first glass material includes at least aluminum phosphate and / or zinc phosphate. The third glass material comprises at least 10% to 20% TiO2, based on the total mass of the third glass material (100%). The softening temperature of the first glass material is lower than that of the second glass material.
2. The electrode paste according to claim 1, characterized in that, Based on the total mass of the mixed glass materials as 100%, the mass content of the first glass material is 10% to 40%, the mass content of the second glass material is 50% to 89%, and the mass content of the third glass material is 1% to 10%.
3. The electrode paste according to claim 1, characterized in that, The first glass material further includes TeO2, PbO, B2O3 and flux. Based on the total mass of the first glass material as 100%, the mass content of TeO2 is 20%~63%, the mass content of PbO is 20%~40%, the mass content of B2O3 is 1%~10%, the mass content of flux is 10%~30%, and the mass content of aluminum phosphate and / or zinc phosphate is 0.5%~1.5%.
4. The electrode paste according to claim 3, characterized in that, The flux includes at least one of Li2O, Na2O, K2O, ZnO, MgO, CaO, SrO, and BaO.
5. The electrode paste according to claim 1, characterized in that, The second glass material comprises TeO2, PbO, Bi2O3, SiO2, WO3, TiO2, ZnO, alkali metal oxides, and alkaline earth metal oxides. Based on the total mass of the second glass material as 100%, the mass content of TeO2 is 15%–35%, the mass content of PbO is 15%–35%, the mass content of Bi2O3 is 10%–25%, the mass content of SiO2 is 15%–30%, the mass content of WO3 is 0%–10%, the mass content of TiO2 is 0%–5%, the mass content of ZnO is 1%–10%, the mass content of alkali metal oxides is 10%–25%, and the mass content of alkaline earth metal oxides is 0%–10%.
6. The electrode paste according to claim 5, characterized in that, The second glass material also includes a silver-containing material, wherein the silver-containing material includes at least one of elemental silver, silver nitrate, and silver oxide; The alkali metal oxides include two or more of Li2O, Na2O, and K2O; The alkaline earth metal oxides include at least one of MgO, CaO, SrO, and BaO.
7. The electrode paste according to claim 1, characterized in that, The third glass material also includes SiO2, B2O3, WO3, Al2O3, ZnO, TeO2, Bi2O3, PbO, and CuO; Based on the total mass of the third glass material as 100%, the mass content of SiO2 is 30%~50%, the mass content of B2O3 is 5%~15%, the mass content of WO3 is 5%~15%, the mass content of Al2O3 is 5%~10%, the mass content of ZnO is 5%~15%, the total mass content of TeO2, Bi2O3 and PbO is 5%~20%, and the mass content of CuO is 5%~15%.
8. The electrode paste according to claim 1, characterized in that, The silver-based conductive material is silver powder, which includes at least one of micron-sized spherical silver powder, micron-sized flake silver powder, dendritic silver powder, and nano-sized spherical silver powder. Based on the total mass of the silver-based conductive material as 100%, the mass content of the micron-sized spherical silver powder is not less than 80%, and the mass content of the nano-sized spherical silver powder is 5%~20%; the particle size D50 of the micron-sized spherical silver powder and the micron-sized flake silver powder is 1μm~5μm, and the particle size D50 of the nano-sized spherical silver powder is 200nm~800nm.
9. A method for preparing an electrode paste according to any one of claims 1 to 8, characterized in that, include: The first glass material, the second glass material, and the third glass material are mixed to obtain a mixed glass material; The silver-based conductive material, the mixed glass material, and the organic carrier are mixed and then ground and dispersed to obtain the electrode slurry.
10. A back-contact solar cell, characterized in that, The electrodes of the back-contact solar cell are formed by printing and sintering the electrode paste according to any one of claims 1 to 8.
